Perception of Patient Safety Culture at the Primary Care Level: The Case of the Community Health Centre Ljubljana - VIRTIČ POTOČNIK Tina; KLEMENC-KETIŠ Zalika (Sciendo, 2024)
Patient safety is a crucial element of quality healthcare, and endeavours to enhance it are vital for attaining universal health coverage and improving patient outcomes. This study aimed to evaluate the perception of patient safety culture among staff at the Community Health Centre Ljubljana (CHCL).